2001
DOI: 10.1067/mva.2001.112318
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of thrombospondin-1 induces vascular smooth muscle cell chemotaxis

Abstract: These results implicate the COOH domain as the portion of the TSP-1 molecule primarily responsible for VSMC chemotaxis. This experiment suggests that future strategies in the prevention of VSMC migration, an initial step in the development of vascular lesions, may involve selective inhibition of the COOH domain of TSP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Thrombospondin-1 (TSP-1) is a member of a protein family that mediates cell-matrix and cell-cell interactions. Experimental data have shown that TSP-1 stimulates the aggregation and stability of platelet aggregates (188), induces the expression of cell adhesion molecules (189) in endothelial cells, and stimulates chemotaxis in vascular SMCs (147,191). In TSP-1 knockout mice, more extensive postinfarction remodeling has been observed compared with wild-type mice (72).…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…Thrombospondin-1 (TSP-1) is a member of a protein family that mediates cell-matrix and cell-cell interactions. Experimental data have shown that TSP-1 stimulates the aggregation and stability of platelet aggregates (188), induces the expression of cell adhesion molecules (189) in endothelial cells, and stimulates chemotaxis in vascular SMCs (147,191). In TSP-1 knockout mice, more extensive postinfarction remodeling has been observed compared with wild-type mice (72).…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 96%
“…In endothelial cells, IL-4 TSP-1 -EC: 1expression of cell adhesion molecules (189) No data available -VSMC: stimulation of chemotaxis (147,191) -1Aggregation and stability of platelet aggregates (188) ACS, acute coronary syndrome; bFGF, basic fibroblast growth factor; CAD, coronary artery disease; CRP, C-reactive protein; EC, vascular endothelial cells; eNOS, endothelial nitric oxide (NO) synthase; IGT, impaired glucose tolerance; IMT, intima-media thickness; iNOS, inducible NO synthase; MMP, matrix metalloproteinase; oxLDL, oxidized low-density lipoprotein; ROS, reactive oxygen species; T2DM, type 2 diabetes mellitus; VSMC, vascular smooth muscle cells.…”
Section: Adipokines With a Tight Link To Cardiovascular Diseasementioning
confidence: 99%
“…TSP-1 is released by platelets, macrophages, monocytes, fibroblasts, vascular smooth muscle cells, and endothelial cells (42,43). TSP-1 has been shown to stimulate and inhibit EC and SMC growth (43,44) and to stimulate and inhibit angiogenesis (45). These contradictory functions have been explained by the use of different experimental approaches and the ability of TSP-1 to interact with various matrix proteins and cell-surface receptors (46).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibits adhesion of G361 melanoma cells (Prater et al and Roberts et al [13,42]). Inhibits TSP-induced chemotaxis of VSMC (Yabkowitz et al and Nesselroth et al [43,44]). Inhibits monocyte haptotaxis (Mansfield and Suchard [45]).…”
Section: E1e2mentioning
confidence: 99%